Heat-shielding film
Patent Information
- Application Number
- JP2025062684
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169039000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a heat-shielding film. [Background technology]
[0002] In modern society, thermal management of buildings, vehicles such as automobiles and trains, and electronic equipment is crucial. For example, if heat rays emitted from sunlight in summer and heat dissipating from indoors in winter can be shielded, indoor temperatures can be appropriately controlled, improving livability, increasing heating and cooling efficiency, and leading to energy savings. It is also possible to protect electronic equipment from external heat, preventing or reducing malfunctions and failures.
[0003] The internal temperature of buildings and electronic equipment can be controlled by applying heat-shielding films to containers such as windows and exterior walls of buildings and casings of electronic equipment (objects to be treated). In particular, applying heat-shielding films to the windows of buildings and equipment can significantly enhance the heat retention and heat shielding effects inside. For this reason, various types of heat-shielding films, especially those with light transmission properties, have been developed over the years.
[0004] For example, Patent Documents 1 and 2 disclose heat-shielding films mainly composed of ITO (indium tin oxide) and resin. These heat-shielding films also possess light transmittance and can be used by being attached to window glass, etc. Patent Document 3 discloses heat-shielding laminated glass in which a resin film with a metal coating layer is sandwiched between two glass plates. In the invention described in Patent Document 3, light transmittance is ensured by making the metal coating layer an island-like structure. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2014-97623 [Patent Document 2] Japanese Patent Publication No. 2015-105325 [Patent Document 3] Japanese Patent Publication No. 2015-205795 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] Conventional heat-shielding films, including those disclosed in Patent Documents 1-3, do not have sufficient light transmittance. For example, when applied to windows of buildings or containers such as display cases, they may reduce the brightness of the room or the visibility inside the container. Conventional heat-shielding films also have the drawback that their transmittance is easily impaired as the heat shielding coefficient decreases. As shown in the comparative examples described later, when the shielding coefficient of many conventional transparent heat-shielding films is plotted against the visible light transmittance (both as dimensionless numbers), the slope value is approximately 0.5 or less (Figure 1). Therefore, if the shielding coefficient is halved, the visible light transmittance may become less than 1 / 4. The relationship between the shielding coefficient and solar transmittance tends to show a similar trend.
[0007] The present invention aims to solve the above-mentioned problems by providing a heat-shielding film that has good heat shielding and light transmission properties and can reduce the shielding coefficient without a significant decrease in visible light transmittance or solar transmittance, as well as window materials and containers equipped with such a heat-shielding film. [Means for solving the problem]
[0008] The inventors have discovered that if a heat-shielding film contains copper sulfide nanoparticles and a specific relationship exists between its absorption coefficient a1 for visible light transmittance and its absorption coefficient a2 for heat shielding, then it can be provided with good heat shielding and light transmittance, and the shielding coefficient can be reduced without a significant decrease in visible light transmittance, thus completing the present invention. The inventors have also found a heat-shielding film in which the shielding coefficient and solar transmittance exhibit a specific relationship. Furthermore, the inventors have discovered that by including a dispersant made of a specific resin together with copper sulfide in the heat-shielding film, the heat shielding and light transmittance can be further improved.
[0009] In other words, the present invention provides the following (1) to (12). (1) A heat-shielding film containing copper sulfide nanoparticles, wherein the content of copper sulfide nanoparticles in 100% by mass of the heat-shielding film is x by mass, and the thickness of the heat-shielding film is t mm, The absorption coefficient a1 for visible light transmittance and the absorption coefficient a2 for (heat) shielding coefficient in the heat-shielding film are given by the following relationship (1): (a2 / a1) × 10 α ≥0.6 (1) (However, let α = (a1 - a2) × x × t.) A heat-shielding film that meets the requirements. (2) A heat shielding film containing copper sulfide nanoparticles, wherein the heat shielding film has a shielding coefficient SC and solar transmittance τ e (Dimensionless number) and the following relationship (2)~(4) SC = b × τ e +c (2) b≧0.4 (3) 0.01 ≤ c ≤ 0.5 (4) A heat-shielding film that meets the requirements. (3) The heat-shielding film of (1) further containing the copper sulfide nanoparticle dispersant. (4) The heat shielding film according to (2) above, further containing the copper sulfide nanoparticle dispersant. (5) A heat-shielding film containing copper sulfide nanoparticles and a dispersant thereof, wherein the dispersant has an SP value of 17 to 28 (MPa) 1 / 2 A heat-shielding film made of resin. (6) Any of the above (1) to (5) heat shielding films, wherein the primary particle size of the copper sulfide nanoparticles is in the range of 1 to 500 nm as measured by dynamic light scattering. (7) A heat-shielding film according to any of (3) to (6) above, wherein the dispersant contains one or more polymers selected from the group consisting of polyvinyl alcohol and polyvinyl butyral having a vinyl alcohol unit content of 15 to 33 mol% and a vinyl acetate unit content of 0.5 to 10 mol%. (8) The heat ray shielding film according to any one of the above (3) to (7), further comprising a binder, wherein the binder contains one or more curable resins selected from the group consisting of (meth)acrylic resins, urethane resins, and epoxy resins, and / or polystyrene. (9) A laminated film having a structure in which the layer of the heat ray shielding film according to any one of the above (1) to (8) is provided on the surface of a transparent base film. (10) A laminate having a structure in which the heat ray shielding film according to any one of the above (1) to (8) is sandwiched between two transparent base materials. (11) One or more light-transmissive base materials selected from the group consisting of glass, polycarbonate resins, and acrylic glass, and The heat ray shielding film according to any one of the above (1) to (8), which is formed on at least one surface of the light-transmissive base material, and A window member comprising the same. (12) One or more light-transmissive containers selected from the group consisting of glass, polycarbonate resins, and acrylic glass, and The heat ray shielding film according to any one of the above (1) to (8), which is formed on at least one of the inner surface and the outer surface of the light-transmissive container, and A container comprising the same. [Effects of the Invention]
[0010] The heat ray shielding film of the present invention has good heat ray shielding properties and light transmittance, and can reduce the heat ray shielding coefficient without causing a significant decrease in visible light transmittance or solar radiation transmittance. Therefore, the window member and container of the present invention provided with such a heat ray shielding film exhibit good heat ray shielding properties and light transmittance, and have the effect of keeping the interior warm and shielding heat while maintaining visibility. [Brief Description of the Drawings]
[0011] [Figure 1] This is a graph plotting each shielding coefficient against the visible light transmittance for the heat ray shielding film according to the present invention and several conventional heat ray shielding films. [Figure 2]This graph shows the shielding coefficients of the heat-shielding films of Examples 1 to 5 plotted against the visible light transmittance. [Figure 3] This graph shows the shading coefficients of the heat-shielding films of Examples 1 to 5 plotted against the solar transmittance. [Figure 4] This is a photographic diagram showing a glass plate equipped with a heat-shielding film according to the present invention, placed on the inside of a windowpane in a building. [Modes for carrying out the invention]
[0012] The present invention will be described in detail below based on several embodiments, but the present invention is not limited to these embodiments.
[0013] Heat-shielding film <First Embodiment> A first embodiment of the present invention is a heat-shielding film containing copper sulfide nanoparticles, wherein the content of copper sulfide nanoparticles in 100% by mass of the heat-shielding film is x by mass, and the thickness of the heat-shielding film is t mm, the absorption coefficient a1 relating to the visible light transmittance (dimensionless) and the absorption coefficient a2 relating to the (heat) shielding coefficient (heat shielding coefficient: dimensionless) in the heat-shielding film are given by the following relation (1): (a2 / a1) × 10 α ≥0.6 (1) (However, let α = (a1 - a2) × x × t.) This is a heat-shielding film that satisfies the following conditions. Such a heat-shielding film combines good heat shielding properties with light transmittance. Note that relation (1) can also be written as follows. (a2 / a1) × 10 (a1-a2)×x×t ≥0.6 (1a) (a2 / a1)×10^{(a1-a2)×x×t}≧0.6 (1b)
[0014] Here, the absorption coefficients a1 and a2 are coefficients in the following relational equations (O1) and (O2), which are approximations devised based on the Lambert-Beer law relating to the visible light transmittance T (dimensionless number) and the (heat ray) shielding coefficient SC (dimensionless number), respectively. Note that the shielding coefficient SC is not the absorbance, but a value that takes into account the absorption rate of infrared rays, which are heat rays. Furthermore, since the shielding coefficient SC is calculated taking into account the reflectance of heat rays, the Lambert-Beer law cannot be directly applied. Therefore, it is assumed that O1 and O2 approximately hold true when the ratio of reflectance to absorptive rate is low. In addition, while the Lambert-Beer law usually uses concentrations in moles, etc., and strictly speaking excludes the contribution of the reflectance component, the approximation equations O1 and O2 in this invention use the concentration of copper sulfide nanoparticles in mass percent units. log[T]=-a1×x×t (O1) log[SC] = -a² × x × t (O²)
[0015] The heat shielding film of this embodiment has good heat shielding properties, and the heat shielding coefficient can be greatly changed by adjusting the content of copper sulfide nanoparticles and the film thickness. As a result, the slope of the plot of the shielding coefficient against visible light transmittance (the ratio of the change in SC ΔSC to the change in T ΔT) is, for example, 0.6 or more, as shown below. Note that the contribution of the reflective component is originally incorporated into the SC value, so there is no need to deliberately separate and calculate it when calculating the change ΔT, etc. Also, even if other sheets are laminated, if the material and thickness of those sheets are the same, it is considered that the amount absorbed or reflected by them is also included in the SC value. ΔSC / ΔT=[d{10^(-a2×x×t)} / dxt] / [d{10^(-a1×x×t)} / dxt] =[-a²×ln10×{10^(-a²×x×t)}] / [-a1×ln10×{10^(-a1×x×t)}] =(a2 / a1)×10^{(a1-a2)×x×t}=(a2 / a1)×10 α From this calculation result and the above relation (1), ΔSC / ΔT ≥ 0.6.
[0016] Thus, in the heat-shielding film of this embodiment, the change in the shielding coefficient ΔSC when the visible light transmittance is changed by ΔT can be 0.6 times or more of ΔT. In other words, the slope of the plot of visible light transmittance against the shielding coefficient can be 1.67 or less. That is, even if the shielding coefficient is reduced, there is no significant decrease in visible light transmittance. Therefore, the shielding coefficient can be reduced without a large decrease in visible light transmittance. Furthermore, it becomes easy to prepare a film with a desired shielding coefficient without significantly changing the visible light transmittance.
[0017] The shielding coefficient can be measured using an infrared spectrophotometer, for example, based on the method described in JIS A5759. The visible light transmittance can be measured using a spectrophotometer, for example, based on the method described in JIS R3106.
[0018] The heat-shielding film of this embodiment can be easily prepared by incorporating copper sulfide nanoparticles, for example, those with a primary particle size in the range of 1 to 500 nm, particularly 1 to 50 nm, as described later. The primary particle size of the copper sulfide nanoparticles can be measured, for example, by dynamic light scattering or image observation using a transmission electron microscope, as described later.
[0019] In actual heat-shielding films, visible light and other light are reflected at the surface, so it is preferable to take these reflectances into account for T, etc. Furthermore, from the viewpoint of improving the transparency of the heat-shielding film, it is desirable that the reflectance of visible light and solar radiation be small, for example, between 0 and 0.5 as a dimensionless number. In practice, it is difficult to make these constants 0, and it is possible to improve the heat-shielding performance by deliberately increasing the reflectance at the surface, but it is preferable to set them to, for example, greater than 0 and 0.45 or less. Specifically, it is preferable that the visible light reflectance be between 0.01 and 0.45, for example between 0.02 and 0.25, and particularly between 0.05 and 0.15, and the solar radiation reflectance be between 0.01 and 0.50, for example between 0.05 and 0.3, and particularly between 0.1 and 0.2.
[0020] The heat ray shielding film of the present embodiment preferably further contains a dispersant for copper sulfide nanoparticles. By containing the dispersant, copper sulfide can be more uniformly and finely dispersed in the heat ray shielding film, so that the light transmittance of the heat ray shielding film can be further improved. As the dispersant, various polymers, particularly those having an SP value of 17 to 28 (MPa) 1 / 2 it is preferable to use a resin of about the above range. Such a dispersant will be described in detail later.
[0021] <Second Embodiment> A second embodiment of the present invention is a heat ray shielding film containing copper sulfide nanoparticles, wherein the shielding coefficient S (dimensionless number) of the heat ray of the heat ray shielding film and the solar transmittance τ e (dimensionless number) satisfy the following relational expressions (2) to (4) S=b×τ e +c (2) b≧0.4 (3) 0.01≦c≦0.5 (4) This is a heat ray shielding film. Such a heat ray shielding film has both good heat ray shielding properties and solar radiation transmittance.
[0022] As shown in the relational expressions (2) to (4), in the heat ray shielding film of the present embodiment, the shielding coefficient can be changed at a degree of 0.4 times or more of the variation of the solar transmittance. In a more preferred embodiment, the value of the slope b is 0.5 to 1.5, particularly 0.6 to 1.0. In other words, the slope of the plot of solar transmittance against the shielding coefficient can be 2.5 or less, further 0.67 to 2.0, particularly 1.0 to 1.67. That is, even if the shielding coefficient is reduced, the solar transmittance does not significantly decrease. Therefore, the shielding coefficient can be reduced without causing a large decrease in the solar transmittance. In addition, it becomes easy to prepare a film having a desired shielding coefficient without largely changing the solar transmittance.
[0023] The solar transmittance can be measured using a spectrophotometer or the like based on, for example, the method described in JIS R3106.
[0024] The heat-shielding film of this embodiment can be easily prepared by incorporating copper sulfide nanoparticles, for example, those with a primary particle size in the range of 1 to 500 nm, particularly 1 to 50 nm, as described later.
[0025] The heat-shielding film of this embodiment preferably further contains a copper sulfide nanoparticle dispersant. The dispersant may be a variety of polymers, particularly those with an SP value of 17-28 (MPa) as described below. 1 / 2 It is preferable to use a resin of a certain degree.
[0026] <Third Embodiment> A third embodiment of the present invention is a heat-shielding film containing copper sulfide nanoparticles and a dispersant thereof, wherein the dispersant has an SP value of 17 to 28 (MPa). 1 / 2 This is a heat-shielding film made of resin. In such heat-shielding films, copper sulfide can be uniformly and finely dispersed, making it easy to achieve good heat shielding and light transmission properties.
[0027] In many of these third embodiment heat-shielding films, the value of relation (1) in the first embodiment is 0.6 or greater. Therefore, the slope determined by the linear regression of the plot of the shielding coefficient against visible light transmittance is, for example, 0.6 or greater. Also, the value of the constant b in the second embodiment is 0.4 or greater. That is, the slope of the plot of the shielding coefficient against solar transmittance is, for example, 0.4 or greater. Thus, the first and second embodiments and the third embodiment overlap in their main components. Furthermore, in all embodiments, "film" refers not only to an independent thin film but also to composite materials with other materials, such as coatings and heat-shielding layers in laminates. In other words, they are all film materials belonging to the same category. Therefore, unless otherwise specified below, the components of the heat-shielding films in these embodiments will be described collectively.
[0028] <Components of heat-shielding film> (copper sulfide) The heat-shielding films of both embodiments described above contain copper sulfide nanoparticles. The inclusion of copper sulfide nanoparticles provides good heat shielding without significant loss of light transmittance. While monovalent copper (Cu2S) and divalent copper (CuS) are well-known as copper sulfide, either type of copper sulfide may be used, and mixtures of both can also be used. Preferably, divalent copper (CuS) is used. This further enhances the heat shielding effect.
[0029] There are no particular restrictions on the size of copper sulfide nanoparticles, but from the viewpoint of improving the transparency of the heat-shielding film, it is preferable that the primary particle diameter is in the range of 1 to 500 nm, and particularly 1 to 50 nm. The primary particle diameter can be measured by methods such as dynamic light scattering. Alternatively, copper sulfide may be selected by observing images of, for example, 200 nanoparticles using a transmission electron microscope, such as when the median primary particle diameter is in the range of 1 to 500 nm, and particularly 1 to 50 nm. The primary particle diameter can also be calculated from the specific surface area measured by methods such as the BET method.
[0030] (Dispersant) The above copper sulfide nanoparticles can be more uniformly dispersed in the heat-shielding film with the presence of a dispersant. Various polymers can be used as dispersants, particularly those with an SP value of 17-28 (MPa). 1 / 2 Resins with the following SP values are preferred. Resins with these SP values have excellent compatibility with copper sulfide (nanoparticles), making it possible to further uniformly and finely disperse copper sulfide nanoparticles in the heat shielding film. Furthermore, even when using solvents and binders described later during the manufacture of the heat shielding film, the dispersion of copper sulfide nanoparticles in these solvents and binders is facilitated by the use of a dispersant. For this reason, the above-mentioned resin dispersant with an SP value is essential for the heat shielding film of the third embodiment, and the heat shielding films of the first and second embodiments also require a dispersant for copper sulfide nanoparticles, particularly one with an SP value of 17-28 (MPa). 1 / 2 It is preferable that the resin contains the following.
[0031] SP value stands for solubility parameter, and it represents the strength of the cohesive force between molecules of a polymer or other substance. Polymers with higher polarity generally tend to have higher SP values. The SP value of a polymer can be determined, for example, by turbidity titration. Specifically, the polymer in question is dissolved in a good solvent with a known SP value, and then a poor solvent with a known SP value is added. The SP value of the mixed solvent when turbidity occurs, i.e., the volume average of the SP values of both solvents, is the SP value of the polymer in question.
[0032] SP value is 17-28 (MPa). 1 / 2 Examples of resins include, but are not limited to, polyvinyl butyral, polyvinyl alcohol, polyurethane, polystyrene, epoxy resin, (meth)acrylic resin, polyvinyl acetate, polyester, polyamide, polyimide, phenolic resin, coumarone-indene resin, halogenated resins such as polyvinyl chloride, and cellulose-based resins including cellulose nitrate. In particular, resins with an SP value of 22-28 (MPa) 1 / 2 Degree, especially 24-27 (MPa) 1 / 2 A resin of a certain degree is preferred.
[0033] The dispersant preferably contains one or more polymers selected from the group consisting of polyvinyl butyral, polyvinyl alcohol, polyurethane, and epoxy resin, and more preferably one or more polymers selected from the group consisting of polyvinyl butyral and polyvinyl alcohol. These resins have excellent compatibility with copper sulfide (nanoparticles) and can further improve the fine dispersion of copper sulfide nanoparticles in the heat shielding film. Polyvinyl butyral is particularly preferred.
[0034] Polyvinyl butyral (PVB) is a resin obtained by reacting polyvinyl alcohol and butyraldehyde under acidic conditions, and typically contains three structural units: vinyl alcohol units, vinyl acetate units, and butyral units. The physical properties of PVB can be controlled by changing the ratio of these three structural units. For example, by setting the vinyl alcohol unit content to 15-33 mol% or the vinyl acetate unit content to 0.5-10 mol%, the SP value can be set to 22-28 (MPa). 1 / 2 It can be set to a certain degree of PVB.
[0035] The dispersant for copper sulfide nanoparticles in a heat-shielding film preferably contains polyvinyl butyral having a vinyl alcohol unit content of 15 to 33 mol%, particularly 16 to 31 mol%. It is also preferable that the dispersant contains polyvinyl butyral having a vinyl acetate unit content of 0.5 to 10 mol%, particularly 0.7 to 3.5 mol%. Using PVB with such a molecular structure as a dispersant allows for more uniform and fine dispersion of copper sulfide nanoparticles in the heat-shielding film, and also makes it easier to mix and disperse the copper sulfide nanoparticles even when solvents or binders are used in combination during the manufacturing of the heat-shielding film. Therefore, it is more preferable that the dispersant contains one or more polymers selected from the group consisting of polyvinyl alcohol and polyvinyl butyral having a vinyl alcohol unit content of 15 to 33 mol% and a vinyl acetate unit content of 0.5 to 10 mol%.
[0036] (binder) The heat-shielding film also preferably contains a binder. The binder fixes the copper sulfide nanoparticles in a finely dispersed state, making it easier to achieve good heat-shielding properties and transparency.
[0037] The type of binder is not particularly limited as long as it does not hinder the dispersibility of copper sulfide nanoparticles; for example, the above-mentioned dispersants may be used as binders. Specific examples include, but are not limited to, various resins and elastomers (organic polymers) such as polyvinyl acetate, poly(meth)acrylic acid (ester), aliphatic polyester, aromatic polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyamide, polyurethane, polyimide, epoxy resin, phenolic resin, silicone resin, fluororesin, polyphenylene oxide, polyphenylene sulfide, polyethersulfone, polyetherketone, polyacrylonitrile, polystyrene, polyester, polypropylene, ABS resin, polyvinyl butyral, styrene-butadiene copolymer, nitrile-butadiene copolymer, and inorganic binders such as cement. Condensates such as alkoxysilanes and silanols, as well as photopolymerizable compounds, can also be used as binders.
[0038] The binder is preferably one or more curable resins selected from the group consisting of (meth)acrylic resins, urethane resins, and epoxy resins, and / or polystyrene. Considering the possibility that the heat-shielding film may become hot when heated during use, the binder is preferably a thermosetting resin. More preferably, a binder containing one or more curable resins selected from the group consisting of (meth)acrylic resins, urethane resins, and epoxy resins is used. Such a binder can fix copper sulfide nanoparticles in the heat-shielding film without impairing the heat-shielding performance. From the viewpoint of light transmittance, an acrylic resin such as poly(meth)acrylic acid (ester) is preferred as the binder.
[0039] The curable resin is preferably a polymer based on (meth)acrylic monomers with an average number of 1 to 6 functional groups, particularly 3 to less than 4. Such monomers and polymers (resins) have the advantage of allowing copper sulfide nanoparticles to be uniformly and finely dispersed. Specific examples include, but are not limited to, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetraacrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate, as well as isobornyl acrylate, phenoxyethyl acrylate, methoxypolyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, and mixtures thereof.
[0040] (Composition of main components) Furthermore, it is preferable to use the binder in combination with the dispersant described above. In a more preferred embodiment of the heat-shielding film, it contains 0.1 to 20% by mass, particularly 3 to 15% by mass, of copper sulfide nanoparticles, 0.1 to 20% by mass, particularly 3 to 18% by mass, of a dispersant, and 60 to 99.8% by mass, particularly 67 to 95% by mass, of a binder, based on the total mass (excluding the base film, etc.). The content here is the value with the total mass of the thin film or coating containing copper sulfide nanoparticles set to 100%. In the case of laminated films or laminates as described later, the total mass of the copper sulfide nanoparticle-containing layer or coating is set to 100%.
[0041] (Additives) In addition to the copper sulfide nanoparticles, dispersant, and binder described above, the heat-shielding film may also contain (fine) particles of inorganic substances other than copper sulfide, surfactants, antioxidants, and additives such as dyes, processing aids used during manufacturing, viscosity modifiers, pH adjusters, and ultraviolet absorbers. However, in order to maintain good heat-shielding and light-transmitting properties, it is preferable to reduce the content of these additives, especially inorganic particles other than copper sulfide. It is preferable that 90% or more, more preferably 95% or more, and especially about 99-99.5% by mass of the components other than the binder in the heat-shielding film, particularly the inorganic particles, are copper sulfide.
[0042] Examples of inorganic particles other than copper sulfide include, but are not limited to, tin-doped indium oxide, aluminum-doped indium oxide, cerium-doped indium oxide, antimond-doped indium oxide (ATO), aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, indium-doped cadmium oxide, fluorine-doped cadmium oxide, chlorine-doped cadmium oxide, bromine-doped cadmium oxide, cesium-doped molybdenum oxide, antimond-doped tin oxide, fluorine-doped tin oxide, titanium oxide, copper sulfide, copper phosphide, copper telluride, copper selenide, ruthenium oxide, rhenium oxide, molybdenum oxide, tungsten oxide, tungsten bronze, nickel sulfide, CuWS4, tungsten-doped TiO2, molybdenum-doped TiO2, Bi2WO6, and other degenerate semiconductors, semimetals, and Mxene.
[0043] <Preparation of heat-shielding film> The heat-shielding film of this embodiment can be prepared, for example, by mixing the above-mentioned copper sulfide nanoparticles with a dispersant and / or binder, and then molding it. There are no particular restrictions on the mixing method; for example, the copper sulfide nanoparticles may be melt-kneaded with a thermoplastic resin used as a dispersant and / or binder. In particular, if the heat-shielding film is a sheet with a certain thickness, it is possible to knead and mold it simultaneously using an extruder or the like to produce the product. Also, when using liquid polymers such as certain epoxy resins or unsaturated polyesters as a binder, they may be mixed with copper sulfide nanoparticles at room temperature and then cured. Alternatively, the copper sulfide nanoparticles and the dispersant and / or binder can be mixed in a solvent to form an ink or paint, which can then be applied to a substrate and dried or cured to prepare the film.
[0044] (Ink / Paint) Among the methods described above, the manufacturing method of mixing copper sulfide nanoparticles with a dispersant and / or binder in a solvent is preferred. In the form of an ink or paint, the heat-shielding film can be easily applied to buildings, vehicles, containers, etc., even to recessed areas. Furthermore, the manufacturing of laminated films and laminates, as described later, is also easy.
[0045] Any solvent may be used as long as it can dissolve the dispersant and binder used and maintains the dispersion state of the copper sulfide nanoparticles. Examples include, but are not limited to, ketones such as methyl ethyl ketone and methyl isobutyl ketone; aliphatic esters such as ethyl acetate; aromatic hydrocarbons such as toluene; halogenated alkyls such as chloroform.
[0046] (coating film) By applying the above-mentioned ink or paint to a substrate, evaporating the solvent to dry it, and further curing it as desired, a coating film can be formed on the surface of the substrate. It is also possible to use a photopolymerizable compound as a binder and form a coating film by photopolymerization.
[0047] Here, if a substrate with a release-type surface is used, the coating (film) formed as described above can be easily peeled off the substrate to obtain a heat-shielding film. Furthermore, when manufacturing laminates, window materials, containers, etc., equipped with a heat-shielding film as described later, it is also possible to use the target window glass, etc., as the substrate and use it as the final product without peeling.
[0048] <Applications of heat-shielding film> The heat-shielding film prepared in this manner exhibits excellent heat-shielding properties and can be applied to various containers such as buildings, building materials, vehicles, vehicle parts, furnace materials, engines, engine components, or parts or casings of electrical or electronic equipment.
[0049] The heat-shielding film of the above embodiment also exhibits light transmittance in addition to heat shielding properties, specifically a visible light transmittance of 0.5 to 1.0 (50 to 100%) and a shielding coefficient of 0.5 to 1.0, typically 0.55 to 0.99, particularly 0.7 to 0.98, and especially 0.8 to 0.95. Moreover, the slope of the plot of the shielding coefficient against visible light transmittance is 0.6 or higher, typically 0.7 to 3.0, particularly around 0.8 to 2.0, and especially around 0.9 to 1.5, so that even when the shielding coefficient is reduced, a significant reduction in visible light transmittance is unlikely. For this reason, it is particularly suitable for applications requiring light transmittance, such as window materials and containers such as showcases.
[0050] The heat-shielding films of these embodiments also exhibit excellent solar transmittance. Specifically, they exhibit a solar transmittance of 0.35 to 1.0 (35 to 100%) along with a shading coefficient of 0.5 to 1.0. Typically, they exhibit a solar transmittance of 0.40 to 0.90 (40 to 90%) and a shading coefficient of 0.55 to 0.99, particularly a solar transmittance of 0.45 to 0.80 (45 to 80%) and a shading coefficient of 0.7 to 0.98. Therefore, even when reducing the shading coefficient, a significant reduction in solar transmittance is unlikely, making them suitable for applications such as window materials. For example, by applying the heat-shielding films of these embodiments to the windows of buildings and equipment, the heat retention and insulation effects inside can be greatly enhanced.
[0051] Laminated film As described above, the heat-shielding film may be used as a standalone product, for example, in the form of a sheet, or it may be a product in which it is applied to a substrate as a coating. As one embodiment of the present invention, the present invention includes a laminated film having a structure in which a layer of the heat-shielding film described above is provided on the surface of a transparent base film. With such a laminated film, the strength and shape are maintained by the transparent base film, which broadens the scope for compositional design of the heat-shielding film (coating) and makes it easier to implement on building materials, etc.
[0052] <Transparent base film> There are no particular restrictions on the type of transparent base film; various polymers, glass, etc., can be used depending on the desired physical properties. Examples include, but are not limited to, polyesters such as polyethylene terephthalate (PET), acrylic resins, and polycarbonate resins. There are also no particular restrictions on its thickness, etc., and it can be set arbitrarily according to the intended product and processing method.
[0053] ≪Laminated structure≫ Another embodiment of the present invention is a laminate having a structure in which the above-mentioned heat-shielding film is sandwiched between two transparent substrates. Such a laminate combines good heat-shielding properties with light transmittance, making it suitable for application to buildings and vehicles, especially their windows and containers such as showcases. Depending on the material of the transparent substrate, the laminate of this embodiment itself can also be used as a window material or a component of a container.
[0054] <Transparent base material> The transparent substrate constituting the laminate can be of any kind, and there are no particular restrictions on its material. Examples include, but are not limited to, glass, acrylic resin, polycarbonate resin, and polymers such as polyethylene terephthalate (PET) and polyester. There are also no particular restrictions on the shape of the transparent substrate; for example, a plate-shaped or film-shaped transparent substrate can be used, but is not limited to these.
[0055] Window materials Another embodiment of the present invention is a window material comprising a translucent substrate made of one or more materials selected from the group consisting of glass, polycarbonate resin, and acrylic glass (acrylic resin), and the above-mentioned heat-shielding film formed on at least one side of the surface of the translucent substrate. Such a window material combines good heat-shielding and light-transmitting properties, making it useful for maintaining an appropriate temperature inside buildings and vehicles and reducing costs such as heating and cooling expenses. For example, by replacing the window glass of a building or vehicle with the window material of this embodiment, it is possible to greatly improve the heat retention and insulation effect inside the room (inside the vehicle). In the window material of this embodiment, the heat-shielding film (coating) may be directly applied to the surface of the translucent substrate, or it may be applied via a transparent base film or transparent substrate in the form of a laminated film or laminate.
[0056] ≪Container≫ Yet another embodiment of the present invention is a container comprising one or more translucent containers selected from the group consisting of glass, polycarbonate resin, and acrylic glass (acrylic resin), and the above-mentioned heat-shielding film formed on at least one of the inner surface and outer surface of the translucent container. Such a container combines good heat shielding and light transmission, and can protect items stored inside a showcase, for example, from external heat without reducing visibility. In this embodiment, the heat-shielding film (coating) may be directly applied to the surface of the translucent container, or it may be applied in the form of a laminated film or laminate via a transparent base film or transparent substrate. [Examples]
[0057] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way to these descriptions.
[0058] Example 1 A heat-shielding film was prepared using a dispersion of purified CuS nanoparticles. The CuS nanoparticles were purified by sequentially ultrasonically washing CuS fine powder in hexane and ethanol, followed by centrifugation and decantation. To the purified CuS nanoparticles, toluene and PVB-1 (polyvinyl butyral with vinyl alcohol content: approximately 28 mol%, vinyl acetate unit content: approximately 2 mol%, SP value: approximately 27, melt viscosity: 20-30 mPa·s) were added and stirred under heating reflux. Hexane was then added and mixed, followed by centrifugation. The supernatant was removed, methyl ethyl ketone (MEK) was added, and the mixture was dispersed under ultrasonic waves. This dispersion was then centrifuged, and the resulting trace amounts of sediment were removed to prepare a dispersion containing CuS nanoparticles (primary particle size 15 nm, concentration 5 mass%) and PVB (concentration 5 mass%) in MEK.
[0059] To prepare the dispersion described above, 2 g of UV-curable acrylic resin (pentaerythritol trimethacrylate / pentaerythritol tetramethacrylate mixture) was dissolved to prepare an ink. This ink was applied to one side of a transparent PET film (25 μm thick), dried at 90°C for 2 minutes, and then crosslinked by irradiation with ultraviolet light at a dominant wavelength of 365 nm for 30 seconds to produce a laminated film-1 with a heat-shielding coating on its surface. The CuS nanoparticle content in the heat-shielding coating was 10.8% by mass, and the film thickness was 10 μm.
[0060] The heat shielding coefficient, visible light transmittance, and visible light reflectance of the obtained laminated film-1 were measured by the following method.
[0061] (Shading coefficient) The shielding coefficient was measured in accordance with JIS A5759. Specifically, a 3mm thick float glass plate was prepared by attaching Nitto Denko's double-sided adhesive tape HJ-9150W to it, and then attaching the back side of laminated film-1 to it. The measurement was performed using a JASCO V-770 spectrophotometer and a JASCO FT / IR-4600 Fourier transform infrared spectrophotometer, following the method described in JIS A5759. The calculated shielding coefficient value was 0.63.
[0062] (Visible light transmittance) The visible light transmittance was measured using a JASCO V-770 spectrophotometer and calculated according to the method described in JIS R3106. The calculated visible light transmittance was 0.5785 (57.85%). This clearly demonstrates that the laminated film-1 possesses both good heat shielding performance and light transmittance. The visible light reflectance was measured using a JASCO V-770 spectrophotometer and was found to be 0.0497 (4.97%).
[0063] Based on the visible light transmittance and shielding coefficient calculated above, a1 and a2 were calculated using relational equations (O1) and (O2). Note that a1 was calculated by substituting the value of T' in the following equation, which is obtained by correcting for the visible light reflectance R (dimensionless number) from the visible light transmittance T, into relational equation (O1). This is to exclude the reflected light amount in order to use the amount of light incident on the heat shielding film-1 as the standard. Furthermore, since the transparent PET film used as the substrate has high transmittance and the absorption of visible light, etc., can be ignored, no correction was made for this. T' = T / (1-R)
[0064] The calculations yielded the values a1=2.00 and a2=1.86. Substituting these into the left side of relation (1), we obtained a value of 1.0, which revealed that laminated film-1 exhibits a large visible light transmittance despite a small heat shielding coefficient.
[0065] (Solar transmittance) For laminated film-1, the same method used for measuring the heat shielding coefficient was applied to a 3mm thick float glass plate. In this state, the solar transmittance and solar reflectance were measured using a JASCO V-770 spectrophotometer according to the method described in JIS R3106. The solar transmittance was 0.3507 (35.07%), and the solar reflectance was 0.0488 (4.88%). When these values were substituted into relational equation (1), etc., along with the shielding coefficient, as with the visible light transmittance mentioned above, a value of 0.8 was obtained. This indicates that the solar transmittance of laminated film-1 is also a large value relative to the heat shielding coefficient.
[0066] Examples 2-3 Laminated films 2 to 3 equipped with a heat-shielding coating were prepared in the same manner as in Example 1, except that the CuS nanoparticle content in the heat-shielding film was 19.4% by mass and the film thickness was 3 μm (Example 2), or the CuS nanoparticle content was 5.7% by mass and the film thickness was 3 μm (Example 3). Visible light transmittance and shielding coefficient were measured. From these values, a1 and a2 were calculated. The results are shown in Table 1 below, along with the results from Example 1.
[0067] Furthermore, regression analysis was performed on the corrected value (T') and shielding coefficient (SC) of the visible light transmittance measured in Examples 1 to 3 against the value of CuS nanoparticle content × film thickness (xt), and the following regression equations were obtained. From these, it is considered that for laminated films 1 to 3 made of the same components, a1 will be approximately 2.04 and a2 will be approximately 1.99. log[T'] = -2.04 × xt (r 2 =0.998) log[S] = -1.99 × xt (r 2 =0.985)
[0068] Furthermore, the shielding coefficients measured in Examples 1 to 3 were plotted against the visible light transmittance, and the slope across the three data points was found to be 1.08. This result, along with the analysis results for Examples 1 to 3, is shown in Table 1 below.
[0069] [Table 1]
[0070] In the laminated films-1 to 3 of Examples 1 to 3, it was revealed that good heat shielding performance and light transmittance were observed. Furthermore, the value on the left side of relation (1) was approximately 1.0 or higher in all cases. It was shown that in this series of heat shielding films, even if the heat shielding coefficient is reduced by adjusting the CuS nanoparticle content or film thickness, there is little risk of a further decrease in visible light transmittance.
[0071] Furthermore, the calculated values of the left-hand side of relational equation (1) in each example showed good agreement with the slope of the plot of the shading coefficient against visible light transmittance in the three data sets of Examples 1 to 3. This demonstrated that the value of the left-hand side of relational equation (1) is useful as a parameter representing the degree of change in one of the two when the other is changed, either the visible light transmittance or the shading coefficient.
[0072] Examples 4-5 Laminated films having a heat-shielding coating were prepared in the same manner as in Examples 1 to 3, except that the CuS nanoparticle content and the thickness of the coating (heat-shielding film) were set to the values shown in Table 2. Visible light transmittance, solar transmittance, and shielding coefficient were then measured. These results, along with the results from Examples 1 to 3, are shown in Table 2 below.
[0073] [Table 2]
[0074] Figures 2 and 3 show graphs plotting these shading coefficient values against visible light transmittance or solar radiation transmittance. In Figure 2, r 2 Under a high correlation of 0.988, a slope of 1.082 was obtained. In Figure 3, r 2 A high correlation of 0.999 was observed, resulting in a slope of 0.714. This once again demonstrates that the heat shielding films in this series do not experience a significant decrease in light transmittance even when the heat shielding coefficient is reduced by adjusting the CuS nanoparticle content or film thickness.
[0075] Furthermore, Figure 4 (right side) shows a photograph of the laminated sheet of this embodiment being attached to the inside of a building windowpane (3 mm thick transparent glass plate) with transparent double-sided adhesive tape. The left side shows a transparent glass plate without the heat-shielding film. It was clearly demonstrated that the heat-shielding film of this embodiment has extremely good light transmittance.
[0076] Furthermore, an experiment was conducted in which the double-glazed sheet of Example 5 was applied to all the window panes of a room and compared with a room in the same environment that had glass windows without the sheet applied. The experiment was conducted in winter, and the material of the glass panes in all cases was general-purpose low-e glass. When the temperature of each room was measured for three days, the room temperature in the room with general-purpose glass windows was about 12-14°C from 9am to 1pm and about 14-18°C from 3pm to 4pm on all days, while the room temperature in the room with the double-glazed glass of this example was about 14-16°C from 9am to 1pm and about 17-20°C from 3pm to 4pm. This demonstrated that even with the same external environment, applying the double-glazed sheet of this example can maintain an indoor temperature about 2°C higher in winter.
[0077] ≪Example 6≫ Except for measuring the shielding coefficient without attaching the sheet to a glass plate, the same procedure as in Example 1 was followed to measure the visible light transmittance and shielding coefficient of the laminated sheet. The plot of the measurement results is shown in Figure 1. The slope determined from the linear regression of this plot was 1.15, which was equivalent to the slope of 1.08 obtained in the regression equations in Examples 1 to 5.
[0078] ≪Comparative Example 1≫ Several types of commercially available heat-shielding film-1 with different thicknesses were prepared, and the shielding coefficient and visible light transmittance were measured for each in the same manner as in Example 1. The plot of the measurement results is shown in Figure 1. The slope of the plot for this commercially available heat-shielding film-1 was 0.45.
[0079] ≪Comparative Example 2≫ The same procedure as in Comparative Example 1 was performed using commercially available heat shielding film-2. The plot of the measurement results is shown in Figure 1. The slope of the plot for this commercially available heat shielding film-2 was 0.54.
[0080] ≪Comparative Example 3≫ The same procedure as in Comparative Example 1 was performed using a commercially available heat-shielding film-3. The plot of the measurement results is shown in Figure 1. The slope of the plot for this commercially available heat-shielding film-3 was 0.28.
[0081] From the above results, it is clear that in the heat shielding film according to the present invention, the slope of the plot of the shielding coefficient against visible light transmittance is well over 0.6, and that reducing the heat shielding coefficient does not result in a significant decrease in visible light transmittance.
[0082] Example 7 Laminates were fabricated using four types of ink prepared in the same manner as in Example 1. Each of the four inks was applied to a release film (50 μm thick), dried at 90°C for 2 minutes, and then cured by irradiation with ultraviolet light at a dominant wavelength of 365 nm for 30 seconds. Subsequently, only the heat shielding film was peeled off the release film, and this was sandwiched between two glass plates and temporarily pressed together. The laminates were then bonded in an autoclave at 121°C and 2 atmospheres for 20 minutes to produce four types of laminates with a structure in which the heat shielding film was sandwiched between two glass plates. When the visible light transmittance and shielding coefficient of these laminates were measured, the plot shown in Figure 1 (▼) was obtained, indicating that the laminates possessed both good heat shielding and light transmittance.
[0083] ≪Reference Examples 1-12≫ A heat-shielding film was attempted to be fabricated in the same manner as in Example 1, except that the polymerizable monomers listed in Table 3 below were used as binders and the PVB listed below was used as a dispersant. PVB-1: Vinyl alcohol content: approx. 27 mol%, vinyl acetate unit content: approx. 2 mol%, SP value: approx. 27, melt viscosity: 20-30 mPa·s PVB-2: Vinyl alcohol content: approx. 27 mol%, vinyl acetate unit content: approx. 2 mol%, SP value: approx. 27, melt viscosity: 35-60 mPa·s PVB-3: Vinyl alcohol content: approx. 19 mol%, vinyl acetate unit content: approx. 2 mol%, SP value: approx. 23, melt viscosity: 35-60 mPa·s PVB-4: Vinyl alcohol content: approx. 36 mol%, vinyl acetate unit content: approx. 2 mol%, SP value: approx. 28, melt viscosity: 30-55 mPa·s
[0084] In each reference example, the dispersion state of CuS nanoparticles during ink preparation was visually evaluated. The results for Reference Examples 1 to 11 are shown in Table 3. In Reference Example 12, where PVB-4 was used as a dispersant, aggregation of some CuS nanoparticles was observed.
[0085] [Table 3]
[0086] As shown in Table 3, the dispersant content of vinyl alcohol units was 15-33 mol%, particularly around 19 mol%, the content of vinyl acetate units was around 2 mol%, and the SP value was 17-28 (MPa). 1 / 2 , especially 23 (MPa) 1 / 2 It was revealed that incorporating PVB can improve the dispersion state of copper sulfide nanoparticles. Furthermore, it was shown that using a curable resin containing a (meth)acrylic monomer with 1 to less than 4 functional groups, particularly 3 to less than 4, as a binder can further improve the dispersion state of copper sulfide nanoparticles.
Claims
1. A heat-shielding film containing copper sulfide nanoparticles, where x mass% is the content of copper sulfide nanoparticles in 100% by mass of the heat-shielding film and t mm is the thickness of the heat-shielding film, the absorption coefficient a1 for visible light transmittance and the absorption coefficient a2 for shielding coefficient in the heat-shielding film are given by the following relation (1): (a2 / a1)×10 α ≧0.6 (1) (However, let α = (a1 - a2) × x × t.) A heat-shielding film that meets the requirements.
2. A heat-shielding film containing copper sulfide nanoparticles, wherein the shading coefficient SC and solar transmittance τ of the heat-shielding film are... e The following relationships are expressed in equations (2) to (4). SC=b×τ e +c (2) b ≥ 0.4 (3) 0.01 ≤ c ≤ 0.5 (4) A heat-shielding film that meets the requirements.
3. The heat-shielding film according to claim 1, further comprising the copper sulfide nanoparticle dispersant.
4. The heat-shielding film according to claim 2, further comprising the copper sulfide nanoparticle dispersant.
5. A heat-shielding film containing copper sulfide nanoparticles and a dispersant thereof, wherein the dispersant has an SP value of 17 to 28 (MPa) 1/2 A heat-shielding film made of resin.
6. The heat-shielding film according to any one of claims 1 to 5, wherein the primary particle size of the copper sulfide nanoparticles is in the range of 1 to 500 nm.
7. The heat-shielding film according to any one of claims 3 to 5, wherein the dispersant contains one or more polymers selected from the group consisting of polyvinyl alcohol and polyvinyl butyral having a vinyl alcohol unit content of 15 to 33 mol% and a vinyl acetate unit content of 0.5 to 10 mol%.
8. The heat-shielding film according to any one of claims 3 to 5, further comprising a binder, wherein the binder comprises one or more curable resins selected from the group consisting of (meth)acrylic resins, urethane resins, and epoxy resins, and / or polystyrene.
9. A laminated film having a structure in which a layer of heat-shielding film according to any one of claims 1 to 5 is provided on the surface of a transparent base film.
10. A laminate having a structure in which a heat-shielding film according to any one of claims 1 to 5 is sandwiched between two transparent substrates.
11. A translucent substrate made of one or more materials selected from the group consisting of glass, polycarbonate resin, and acrylic glass, A heat-shielding film according to any one of claims 1 to 5, formed on at least one side of the surface of the light-transmitting substrate. Window material equipped with [a specific feature / feature].
12. A translucent container made of one or more materials selected from the group consisting of glass, polycarbonate resin, and acrylic glass, A heat-shielding film according to any one of claims 1 to 5, formed on at least one side of the inner surface and outer surface of the light-transmitting container. A container equipped with [the following features].
Citation Information
Patent Citations
Heat-ray shielding film
JP2014097623A
Transparent resin composition, coating film, and heat ray shielding film
JP2015105325A
Heat ray-shielding glass laminate
JP2015205795A